Freedom an unruly history - Dijn, Annelien de 1977- (ProQuest Ebook Central, 2020)
Cover -- Title Page -- Copyright -- Contents -- Introduction: An Elusive Concept -- Part I. The Long History of Freedom -- 1. Slaves to No Man: Freedom in Ancient Greece -- 2. The Rise and Fall of Roman Liberty -- Part II. Freedom's Revival -- 3. The Renaissance of Freedom -- 4. Freedom in the Atlantic Revolutions -- Part III. Rethinking Freedom -- 5. Inventing Modern Liberty -- 6. The Triumph of Modern Liberty -- Epilogue: Freedom in the Twenty-First Century -- Notes -- Acknowledgments -- Illustration Credits -- Index.